A new name in New Guinea Saurauia Willd. (Actinidiaceae). Issue 4 (December 2015) - Briggs, Marie
Summary Saurauia spinosa is proposed as a new name forSaurauia horrida Kaneh. & Hatus. non Hook. f. from New Guinea. Photographs of this species are provided.